2023
DOI: 10.1037/pha0000568
|View full text |Cite
|
Sign up to set email alerts
|

From if-then to here and now: Using personalized counterfactuals from past negative experiences to reduce future alcohol consequences.

Abstract: College students are at an increased risk for problematic alcohol use. To address this health concern, several interventions have used protective behavioral strategies (PBS). However, interventions promoting PBS remain underdeveloped and underutilized. Counterfactual thinking is a type of postmortem cognitive strategy that highlights causal links between a behavior and a negative outcome. Recent research demonstrates the effectiveness of applying counterfactuals for increasing PBS use intentions. The present s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 59 publications
0
1
0
Order By: Relevance
“…This suggests a need for increased processes of change use. Recent research has demonstrated the utility of pairing a counterfactual intervention with protective behavioral strategies to decrease alcohol intake among young adults (Smallman et al, 2022). In a similar vein, future work should look at using a counterfactual intervention to prompt participants to incorporate processes of change within the counterfactual content.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests a need for increased processes of change use. Recent research has demonstrated the utility of pairing a counterfactual intervention with protective behavioral strategies to decrease alcohol intake among young adults (Smallman et al, 2022). In a similar vein, future work should look at using a counterfactual intervention to prompt participants to incorporate processes of change within the counterfactual content.…”
Section: Discussionmentioning
confidence: 99%